Valuable Hepatoprotective Plants - How Can We Optimize Waste Free Uses of Such Highly Versatile Resources? - Krepkova, Lubov V.; Babenko, Aleksandra N.; Saybel’, Olga L.; Lupanova, Irina A.; Kuzina, Olga S.; Job, Kathleen M.; Sherwin, Catherine M.; Enioutina, Elena Y. (Frontiers in Pharmacology, 2021)
Humans used plants for thousand of years as food, drugs, or fuel to keep homes warm. People commonly used fruits and roots, and other parts of the plant were often wasted. This review aims to discuss the potential of rational stem-to-stern use of three highly versatile and valuable plants with hepatoprotective properties. Milk thistle (Silybum marianum L. Gaertn.), artichoke (Cynara cardunculus), and chicory (Cichorium intybus L.) have well-characterized hepatoprotective properties. These plants have been chosen since liver diseases are significant diseases of concern worldwide, and all parts of plants can be potentially utilized. Artichoke and chicory are commonly used as food or dietary supplements and less often as phytodrugs. Various dietary supplements and phytodrugs prepared from milk thistle (MT) fruits/seeds are well-known to consumers as remedies supporting liver functions. However, using these plants as functional food, farm animal feed, is not well-described in the literature. We also discuss bioactive constituents present in various parts of these plants, their pharmacological properties Distinct parts of MT, artichoke, and chicory can be used to prepare remedies and food for humans and animals. Unused plant parts are potentially wasted. To achieve waste-free use of these and many other plants, the scientific community needs to analyze the complex use of plants and propose strategies for waste-free technologies. The government must stimulate companies to utilize by-products. Another problem associated with plant use as a food or source of phytodrug is the overharvesting of wild plants. Consequently, there is a need to use more active cultivation techniques for plants.